DETERMINING FACTORS FOR EXCLUSIVE BREASTFEEDING IN THE UPT WORKING AREA OF SEBANGAR COMMUNITY HEALTH CENTERBENGKALIS REGENCY IN 2023 - Prima yanti; Nur Afrinis; Milda Hastuty (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Exclusive breast milk is the ideal food for baby growth and development. The problem is that coverage of exclusive breastfeeding is still low due to the failure of exclusive breastfeeding. The success of breastfeeding is influenced by motivational factors, mother's work and family support. Data from the UPT Puskesmas Sebangar in 2021 saw a decline in coverage of exclusive breastfeeding, namely 59.1% in 2021, down to 38.9% in 2022.Research objectives forfind out the determining factors for exclusive breastfeeding at the UPT Puskesmas Sebangar, Bengkalis Regency in 2023.This research is a quantitative cross sectional design.The research was carried out from dateJuly 12-24 2023.Population of 85 mothers and babies aged 6-12 months in the working area of ??the UPT Puskesmas Sebangarusing total sampling technique.Data analysis used univariate and bivariate analysis with the Chi-Square test. The research results obtained were 44 respondents (51.8%) with high motivation, 56 respondents (65.9%) did not work, 46 respondents (54.1%) had supportive families, 52 respondents (61.2%) did not breastfeed exclusive. There is a relationship between motivation (p value = 0.004) andfamily support(p value = 0.000)with exclusive breastfeeding. There is no relationship between employment (p value = 0.560) and exclusive breastfeeding. It is recommended that UP UPT Puskesmas Sebangar provide pemguidance and counseling to increase mother's motivation increases and changes in behavior occur mother to provide exclusive breastfeeding.